Southern Islands Vascular Flora (SIVFLORA) dataset: A global plant database from Southern Ocean islands - Pablo C. Guerrero; Tamara Contador; Angie Díaz; Catalina Escobar; Julieta Orlando; Catalina Marín; Patricio Medina (Scientific Data)
Abstract The Southern Islands Vascular Flora (SIVFLORA) dataset is a globally significant, open-access resource that compiles essential biodiversity data on vascular plants from islands across the Southern Ocean. The SIVFLORA dataset was generated through five steps: study area delimitation, compiling the dataset, validating and harmonizing taxonomy, structuring dataset attributes, and establishing file format and open access. Covering major taxonomic divisions, SIVFLORA offers a comprehensive overview of plant occurrences, comprising 14,589 records representing 886 species, 95 families, and 42 orders. This dataset documents that 58.62% of the taxa are native, 9.61% are endemic, and 31.77% are alien species. The Falkland/Malvinas Archipelago, the most species-rich, contrast sharply with less diverse islands like the South Orkney Archipelago. SIVFLORA serves as a taxonomically harmonized, interoperable resource for investigating plant diversity patterns, ecosystem responses to climate change in extreme environments, island biogeography, endemism, and the effects of anthropogenic pressures on Southern Ocean flora.